Validity and reliability of a questionnaire on knowledge, attitude, practice and perception (KAP2) towards food poisoning and its prevention during dining out among consumers in Terengganu - Nur Afifah, M.Z.; Asma', A.; Raihana, N.I.; Malina, O.; Chee, H.Y.; Misni, N.; Sukeri, S.; Chin Pei Yee (Rynnye Lyan Resources, 2021)
Having adequate knowledge, attitude, practice, and realistic perception (KAP2) of food poisoning prevention will minimize the risk of food poisoning while dining out. However, there is no validated KAP2 questionnaire on the prevention of food poisoning during dining out, notably among consumers. Throughout the current research, a validated KAP2 questionnaire on food poisoning and prevention during dining was developed. A cross-sectional pilot survey was conducted among 30 selected consumers in Kuala Nerus, Terengganu. Convenience sampling was applied to the recruitment of consumers based on inclusion and exclusion criteria. The KAP2 questionnaire comprised the knowledge section (42 questions), attitude (15 questions), practice (13 questions) and the perception (15 questions). Knowledge questions were analysed using difficulty and discrimination index, while attitude, practice, and perception were analysed by construct validity and reliability analysis. The difficulty index with less than 0.3 is considered as difficult, between 0.30-0.70 as an acceptable value, and more than 0.70 as easy. The discrimination index below than 0.2 is considered poor, between 0.2-0.24 as good, more than 0.35 as excellent items. The construct validity was conducted by referring to the value of Cronbach's alpha, inter-item correlation (˃ 0.30), item-total correlation (˃ 0.30), and Cronbach's alpha if item deleted. The results were found from 42 knowledge items, 29 easy items, ten acceptable items and three difficult questions. The discrimination index revealed that 25 items were poor, 11 items were excellent, three items had a good discrimination index and three items needed to be revised. Based on construct validity, five attitude’s items, three practice’s items and ten perception’s items were removed due to inter-item correlation and item-total correlation value < 0.30. The reliability analysis of the attitude portion was 0.848 which is a good reliability, 0.780 practice, and 0.611 perceptions to be found an acceptable value of reliability. Overall, the developed KAP2 questionnaire is a valid and reliable questionnaire that can serve as an evaluation tool for measuring knowledge, attitudes, practice and perception in the prevention of food poisoning during dining out among consumers.